1995
DOI: 10.1038/bjc.1995.481
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endogenous cytokines, adhesion molecules and platelets during cytokine-induced tumour necrosis

Abstract: Summarv The aim of this study was to investigate mechanisms of anti-tumour activity and necrosis induced bv combinations of tumour necrosis factor alpha (TNF-x) and interferon gamma (IFN-y) The concept of inducing haemorrhagic necrosis to treat tumours was first investigated systematically by Coley (1893). However, it was not until 1975 that a tumour-necrosing activity in the sera of BCG-pnrmed endotoxin treated mice was isolated (Carswell et al.. 1975). Since then, two molecules responsible for this activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Taking into account the time-point of the cell inoculations (days 10 and 12 of pregnancy), we believe that the vessel damage was induced by direct interaction between the vessels and immune cells that secreted Th1 cytokines. Indeed, Th1-cytokines are sufficient for destruction of tumor vasculature in animal models [46]. In our model, activated cells as well as the augmented secretion of TNF- § , IFN-+ or IL-12 may contribute to the vessel alterations observed at the feto-maternal interface.…”
Section: Discussionmentioning
confidence: 93%
“…Taking into account the time-point of the cell inoculations (days 10 and 12 of pregnancy), we believe that the vessel damage was induced by direct interaction between the vessels and immune cells that secreted Th1 cytokines. Indeed, Th1-cytokines are sufficient for destruction of tumor vasculature in animal models [46]. In our model, activated cells as well as the augmented secretion of TNF- § , IFN-+ or IL-12 may contribute to the vessel alterations observed at the feto-maternal interface.…”
Section: Discussionmentioning
confidence: 93%
“…Bone marrow transfer studies using CXCL16-deficient mice are warranted to ascertain the respective contributions of infiltrating versus resident renal cells toward the renal expression of CXCL16 (and the other implicated molecules) during immune nephritis. Although these 4 molecules have been discussed as independent entities, it is certainly possible that they may be coordinately regulated during disease, and there is some evidence to support this possibility (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that co-administration of TNF with IFN-, a pleiotropic cytokine mainly produced by Tlymphocytes and natural killer cells and in minor amounts by B-lymphocytes, macrophages, and dendritic cells [33][34][35][36][37][38], potentiates its antitumour properties in a variety of murine tumours and human xenografts [39][40][41]. Moreover, combined treatment of endothelial or tumour cells with TNF and IFN-γ results in synergistic cytotoxic eff ects [42][43][44].…”
Section: Ngr-tnfmentioning
confidence: 97%